Effects of Age and Disease Severity on Systemic Corticosteroid Responses in Asthma - Phipatanakul, Wanda; Mauger, David T.; Sorkness, Ronald L.; Gaffin, Jonathan M.; Holguin, Fernando; Woodruff, Prescott G.; Ly, Ngoc P.; Bacharier, Leonard B.; Bhakta, Nirav R.; Moore, Wendy C.; Bleecker, Eugene R.; Hastie, Annette T.; et al. (American journal of respiratory and critical care medicine, 2017)
Phenotypic distinctions between severe asthma (SA) and nonsevere asthma (NONSA) may be confounded by differential adherence or incorrect use of corticosteroids. To determine if there are persistent phenotypic distinctions between SA (as defined by 2014 American Thoracic Society/European Respiratory Society guidelines) and NONSA after intramuscular triamcinolone acetonide (TA), and to identify predictors of a corticosteroid response in these populations. A total of 526 adults age 18 years and older (315 SA) and 188 children age 6 to less than 18 years (107 SA) in the NHLBI Severe Asthma Research Program III were characterized before and 3 weeks after TA. The primary outcome for corticosteroid response was defined as greater than or equal to 10-point improvement in percent predicted FEV . Adult asthma groups exhibited a small but significant mean FEV % predicted improvement after TA (SA group mean difference, 3.4%; 95% confidence interval, 2.2-4.7%; P = 0.001), whereas children did not. Adult SA continued to manifest lower FEV and worse asthma control as compared with NONSA after TA. In children, after TA only prebronchodilator FEV distinguished SA from NONSA. A total of 21% of adults with SA and 20% of children with SA achieved greater than or equal to 10% improvement after TA. Baseline bronchodilator response and fractional exhaled nitric oxide had good sensitivity and specificity for predicting response in all groups except children with NONSA. One in five patients with SA exhibit greater than or equal to 10% improvement in FEV with parenteral corticosteroid. Those likely to respond had greater bronchodilator responsiveness and fractional exhaled nitric oxide levels. In adults, differences in airflow obstruction and symptoms between SA and NONSA persist after parenteral corticosteroids, suggesting a component of corticosteroid nonresponsive pathobiology in adults with SA that may differ in children. Clinical trial registered with www.clinicaltrials.gov (NCT 01606826).